Youth Perspectives on Technological Modernization for Sustainable Beef Cattle Agribusiness Regeneration in Mamasa, Indonesia - Muhammad Nur Rustan; Sulaiman; Abdurrahman Rustam Hakim (Tarjih : Agribusiness Development Journal, 2026)
The aging livestock farmer phenomenon and low youth participation threaten the sustainability of smallholder beef cattle agribusiness. This study aims to analyze the effect of technological modernization on the regeneration interest of young livestock farmers in Mamasa Regency. An explanatory quantitative approach was employed, involving 73 youth respondents from farming families selected via purposive sampling. Primary data were collected using questionnaires and analyzed with Structural Equation Modeling-Partial Least Square (SEM-PLS). The results demonstrated that perceived operational ease through mechanization, expectation of financial gain via digital marketing, and social image improvement from modern infrastructure partially and simultaneously have a positive and significant impact on youth regeneration interest. The expectation of financial gain proved to be the most dominant pull factor. In conclusion, technological modernization serves as a robust catalyst to dismantle the stigma of manual labor and foster agribusiness succession. Therefore, it is recommended that the government transitions from providing partial agricultural assistance to developing an integrated innovation ecosystem, while rural youth are encouraged to establish millennial farmer institutions to strengthen market bargaining power.